The Symmetric Linear Rational Expectations Model - Kollintzas, Tryphon (Econometrica, 1985)
[For many multivariate linear rational expectations models a symmetry condition is satisfied, and when it is, a convenient representation of the solution exists that has many of the desirable features of the solution to the univariate model. This allows for greater insight into the identification, stability, and comparative dynamics properties of the model.]